Implementasi Pendekatan Neurosains pada Pembelajaran IPS untuk Menumbuhkan Sikap Sosial Siswa Sekolah Dasar - Arina Wulandari; Muhammad Arifin; Wulida Makhtuna (Jurnal Ilmiah Multidisiplin Mahasiswa dan Akademisi, 2026)
This study aims to describe the implementation of the neuroscience approach in Social Studies (IPS) learning and its impact on elementary school students’ social attitudes. This research employed a qualitative descriptive method. The participants included the principal, a fifth-grade teacher, and students at SDN 2 Loktabat Selatan Banjarbaru. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model. The results show that the neuroscience-based learning approach was implemented through structured lesson planning, active learning activities such as group discussions, visual media use, brain gym activities, and reflection sessions. The learning process created an engaging and enjoyable classroom atmosphere that increased students’ participation and interaction. The findings also reveal positive improvements in students’ social attitudes, including cooperation, responsibility, empathy, tolerance, discipline, and communication skills. Supporting factors include teacher competence, school support, and students’ active characteristics, while inhibiting factors include limited time allocation, inadequate learning facilities, and uneven understanding of neuroscience concepts among teachers. Overall, the neuroscience approach proved effective in improving the quality of Social Studies learning and fostering students’ social attitudes in elementary education.